2021
DOI: 10.1097/phh.0000000000001446
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Community-Based Organizations Funded by the Centers for Disease Control and Prevention's HIV Testing Program

Abstract: Context: HIV testing is a critically important first step in preventing and reducing HIV transmission. Community-based organizations (CBOs) are uniquely positioned to provide HIV testing and other prevention services to populations disproportionately affected by HIV infection. Objective: The purpose of this analysis was to assess CDC-funded health department (HD) and CBO testing programs during 2012-2017, including the number of tests and HIV positivity. Design: This is an analysis of National HIV Prevention P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…For example, this study found that participating in activities conducted by CBOs and receiving HIV-related information through social media were positively associated with HIV testing uptake. To date, the CBOs have played an essential role in addressing determinants of health through their formal and informal medical and social services [30,31], and social media have been widely used in HIV prevention programs [32,33]. More programs including education on HIV prevalence and HIV risk assessment with consulting service could be conducted by CBOs through activities or through social media to make MSM understanding the HIV risk better and seek testing services routinely.…”
Section: Discussionmentioning
confidence: 99%
“…For example, this study found that participating in activities conducted by CBOs and receiving HIV-related information through social media were positively associated with HIV testing uptake. To date, the CBOs have played an essential role in addressing determinants of health through their formal and informal medical and social services [30,31], and social media have been widely used in HIV prevention programs [32,33]. More programs including education on HIV prevalence and HIV risk assessment with consulting service could be conducted by CBOs through activities or through social media to make MSM understanding the HIV risk better and seek testing services routinely.…”
Section: Discussionmentioning
confidence: 99%
“…Non–health care sites, particularly community-based organizations (CBOs), are known and trusted by their communities and have culturally competent providers of HIV testing and referrals to HIV care and PrEP sites27 and thus able to make a substantial impact with persons at risk for HIV acquisition and persons with newly diagnosed HIV. For example in 1 study, being tested for HIV and receiving free condoms from an HIV/AIDS CBO were associated with PrEP awareness 28.…”
Section: Discussionmentioning
confidence: 99%
“…24 Interventions that might be effective to increase PrEP awareness among Hispanic/Latino persons include social media strategies, social marketing, community education materials, peer networks, support groups, and culturally and linguistically competent staff. 25,26 Non-health care sites, particularly communitybased organizations (CBOs), are known and trusted by their communities and have culturally competent providers of HIV testing and referrals to HIV care and PrEP sites 27 and thus able to make a substantial impact with persons at risk for HIV acquisition and persons with newly diagnosed HIV. For example in 1 study, being tested for HIV and receiving free condoms from an HIV/AIDS CBO were associated with PrEP awareness.…”
Section: Discussionmentioning
confidence: 99%